Spray Characteristics and Internal Flow Structures of Swirl Effervescent Atomizer - A. Ghaffar, Z; Kasolang, S; H. A. Hamid, Ahmad (International Journal of Engineering and Technology, 2018)
Spray characteristics and internal flow structures of an atomizer are important parameters in indicating their performances. Both parameters are affected by the operating conditions and atomizer geometries. This study investigates the effect of operating parameters and atomizer geometries on spray angle, breakup length and gas core diameter of swirl effervescent atomizer. This work is conducted specifically to find the most critical parameters that will produce the required spray characteristics and internal flow structure. The atomizer performance tests were carried out using water as the working fluid and nitrogen gas as the atomizing agent. High-speed shadowgraph technique was utilized to record the videos of the spray and internal flow structures. The video recordings were converted to image sequences and analyzed using image processing software. Geometrical parameters were found to be more dominant for characterizing the resultant sprays, but operating conditions was more critical in affecting the internal flow structures. The widest spray angle ( 25Â°) and shortest breakup length ( 10mm) were observed at the high level of swirl-generating vane angle and discharge orifice diameter. Gas core diameter expanded up to 1.13mm at the high level of GLR.Â Â